Acheulean variability in Western Europe: The case of Menez-Dregan I (Plouhinec, Finistère, France). Issue 162 (January 2022) - Ravon, Anne-Lyse; García-Medrano, Paula; Moncel, Marie-Hélène; Ashton, Nick
Abstract: The establishment of the Acheulean in Europe occurred after MIS 17, but it was after the harsh glaciation of MIS 12 and during the long interglacial of MIS 11 that human occupation of Western Europe became more sustained, with an increased number of sites. Menez-Dregan I (Brittany, France) is one of the key sites in Western Europe that dates from this threshold, with an alternating sequence of 16 occupation levels and four marine deposits, from MIS 12 to 8. The large lithic assemblages of more than 154, 000 artifacts from knapping (cores, flakes) and shaping (macrotools and shaping flakes) show the varying use of raw materials and activities at the site through the sequence. This work focuses on the study of the handaxes and cleavers using technological and metrical methods with multivariate analysis, in combination with geometric morphometrics, and places these analyses within the context of other technological changes at the site. Collectively, results show the persistent use through the sequence of the same lithic raw materials and technologies, including fire use and the import of glossy sandstone from 20 km away, but with variation in activities at the site. These findings suggest that Menez-Dregan I shows the development of a specific material culture that reflects the local resources and environment. Results further indicate that the site shows the sustained hominin occupation of the area, despite varying climate and environment, with strong traditions of social learning that were maintained through flexibility of site use, deep understanding of the local territory, and the innovation of new technologies, such as the use of fire. Evidence from the site is placed within the wider context of Europe, and contrasted with areas to the north, such as Britain, where hominin occupation was more sporadic and driven by cyclical climate change.